Detox agents do not affect the pharmacokinetics of methamphetamine in the rat - Lee, Sang Kyu; Kim, Yoon; Suh, SungIll; Suh, Yong Jun; In, Moon Kyo; Kim, Dong-Hyun; Jin, Changbae; Yoo, Hye Hyun (ELSEVIER IRELAND LTD, 2009)
Recently, 'detox' agents have been popularly used as forms of diets or nutritional supplements. Especially, several cases have been reported that these detox agents have been used to mask drug tests among drug abusers. In the present study, capsule and drink types of detox agents were evaluated for their ability to alter the elimination of methamphetamine (MA) in rats. For this study, MA and its major metabolite, amphetamine (AP) in urine samples were determined using LC-tandem mass spectrometry after administration of the detox agents to MA-treated rats. As a result, significant differences were not shown between control and detox-dosed groups in the amounts of MA and AP excreted into urine as well as the volume of excreted urine. This result suggests that the detox agents tested may not affect the metabolism or elimination of MA and further might have minimal effect on narcotics detection in the urine samples of drug abusers. (C) 2009 Elsevier Ireland Ltd. All rights reserved.